Four-week progressive unilateral plyometric training improves vertical jump height in youth football goalkeepers - Luthfi Adhitya; Jeki Haryanto; Vega Soniawan; Ikhwanul Arifan (Global Econedu, 2026)
Goalkeepers perform a vertical jump with one-leg many times when contesting crosses, corners, and lofted passes while plyometric training studies that are related to football have mainly concentrated on outfield players, thus leaving the position-specific evidence for goalkeepers scarce. This study investigated the impacts of unilateral plyometric training program of 16 sessions on the explosive power of lower limbs of youth football goalkeepers. Using a quasi-experimental one-group pretest-posttest design, six male goalkeepers (13.8 ± 1.5 years; 4.2 ± 1.1 years of playing experience) recruited by purposive sampling from a community football academy in Padang, Indonesia participated in the study. The vertical jump wall-and-chalk test was used to assess lower limb explosive power, with the best of three jumps used for analysis. The training intervention involved eight progressive variations of the cone-assisted single-leg plyometric exercises carried out in 16 sessions (four times a week for four weeks), three sets of eight, seven and six repetitions at 90%, 95% and 100% maximal effort respectively, with 1-3 min inter-set and 5 min inter-drill recovery were prescribed. Normality was verified through the Lilliefors test, variance homogeneity through an F ratio, and the hypothesis through a paired-samples t-test complemented by standardised effect sizes and 95% confidence intervals. Vertical jump height rose from 29.83 ± 9.15 cm to 34.67 ± 9.31 cm, a mean increase of 4.83 cm (95% CI [1.98, 7.68]), t(5) = 4.36, p = .007, dz = 1.78. Each participant enhanced their performance (range 2-10 cm; +16.2% group mean). Therefore, short-cycle unilateral plyometrics can be considered as a low-cost, equipment-light strategy that coaches can easily integrate into regular goalkeeper training sessions to improve aerial-dual readiness.